Use of the Coding Causes of Death in HIV in the classification of deaths in Northeastern Brazil - Diana Neves Alves; Cristiane Campello Bresani-Salvi; Joanna d'Arc Lyra Batista; Ricardo Arraes de Alencar Ximenes; Demócrito de Barros Miranda-Filho; Heloísa Ramos Lacerda de Melo; Maria de Fátima Pessoa Militão de Albuquerque (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Describe the coding process of death causes for people living with HIV/AIDS, and classify deaths as related or unrelated to immunodeficiency by applying the Coding Causes of Death in HIV (CoDe) system. METHODS A cross-sectional study that codifies and classifies the causes of deaths occurring in a cohort of 2,372 people living with HIV/AIDS, monitored between 2007 and 2012, in two specialized HIV care services in Pernambuco. The causes of death already codified according to the International Classification of Diseases were recoded and classified as deaths related and unrelated to immunodeficiency by the CoDe system. We calculated the frequencies of the CoDe codes for the causes of death in each classification category. RESULTS There were 315 (13%) deaths during the study period; 93 (30%) were caused by an AIDS-defining illness on the Centers for Disease Control and Prevention list. A total of 232 deaths (74%) were related to immunodeficiency after application of the CoDe. Infections were the most common cause, both related (76%) and unrelated (47%) to immunodeficiency, followed by malignancies (5%) in the first group and external causes (16%), malignancies (12 %) and cardiovascular diseases (11%) in the second group. Tuberculosis comprised 70% of the immunodeficiency-defining infections. CONCLUSIONS Opportunistic infections and aging diseases were the most frequent causes of death, adding multiple disease burdens on health services. The CoDe system increases the probability of classifying deaths more accurately in people living with HIV/AIDS.